Anterior placental location influences onset and progress of labor and postpartum outcome. Issue 4 (April 2015) - Torricelli, M.; Vannuccini, S.; Moncini, I.; Cannoni, A.; Voltolini, C.; Conti, N.; Di Tommaso, M.; Severi, F.M.; Petraglia, F.
Abstract Introduction The aim of the study is to evaluate whether placental location at term is associated with delivery outcome. Methods A prospective study including 2354 patients with singleton pregnancy at term admitted for vaginal delivery was conducted. Placental position was determined before delivery by ultrasonographic examination performed transabdominally with women in the supine position. Maternal characteristics and delivery outcome such as premature rupture of membranes, induction of labor, mode and gestational age at delivery, indication for cesarean section, duration of the third stage, postpartum hemorrhage (PPH) and manual removal of placenta were correlated with anterior, posterior or fundal placental locations. Results Among women enrolled: i) 1164 had an anterior placenta, ii) 1087 a posterior placenta, iii) 103 a fundal placenta. Women with anterior placenta showed: i) a higher incidence of induction of labor (p = 0.0001), especially for postdate pregnancies and prolonged prelabor rupture of membranes (p < 0.0001), ii) a higher rate of cesarean section rate for failure to progress in labor (p = 0.02), iii) a prolonged third stage (p = 0.01), iv) a higher incidence of manual removal of placenta (p = 0.003) and a higher rate of PPH in vaginal deliveries (p = 0.02). Discussion The present study showed the influence of anterior placental location on the course of labor, with a later onset of labor, a higher rate of induction and cesarean section and postpartum complications. The reason for this influence on labor and delivery complications remains to be elucidated.